PENINGKATAN MUTU LAYANAN MELALUI IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA DI MAN 2 BANDUNG - Euis Kurnia Handayani (UNISAN JURNAL, 2024)
This research aims to explore the implementation of human resource management (HR) at MAN 2 Bandung, Bandung Regency and its impact on improving the quality of educational services at this institution. Using a qualitative approach and case study design, data was collected through in-depth interviews, participant observation and documentation studies. The research results show that the implementation of HR management at MAN 2 Bandung includes a transparent recruitment and selection process, career development through training and development programs, as well as regular performance evaluations. Factors that influence the implementation of HR management include limited resources, government regulations, organizational culture, and leadership. However, effective implementation has positive impacts, including improved teacher and staff performance, high motivation and job satisfaction, and improved working relationships among institutional members. This impact is reflected in the improvement in the quality of educational services, which is characterized by better learning effectiveness, a more meaningful educational experience for students, and increased academic achievement. In conclusion, the implementation of HR management at MAN 2 Bandung, Bandung Regency has an important role in improving the quality of educational services provided by this institution. Keywords: Service Quality, Human Resource Management